2014
DOI: 10.3390/nano5010047
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake of Tile-Assembled DNA Nanotubes

Abstract: DNA-based nanostructures have received great attention as molecular vehicles for cellular delivery of biomolecules and cancer drugs. Here, we report on the cellular uptake of tubule-like DNA tile-assembled nanostructures 27 nm in length and 8 nm in diameter that carry siRNA molecules, folic acid and fluorescent dyes. In our observations, the DNA structures are delivered to the endosome and do not reach the cytosol of the GFP-expressing HeLa cells that were used in the experiments. Consistent with this observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 36 publications
3
46
0
4
Order By: Relevance
“…Clearly this is a physical factor that must be considered in the assembly of well-defined cellular structures from mechanically dissimilar, filamentous, biopolymer components such as actin, microtubules, vimentin and keratin. Additionally, the broad interest in applying DNA-based macromolecules, often those of an extended rod-like geometry and in the size regime subject to crowding effects [16,[45][46][47][48], as intracellular therapeutics, suggests that this basic assembly mechanism should be considered. Figure A3.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly this is a physical factor that must be considered in the assembly of well-defined cellular structures from mechanically dissimilar, filamentous, biopolymer components such as actin, microtubules, vimentin and keratin. Additionally, the broad interest in applying DNA-based macromolecules, often those of an extended rod-like geometry and in the size regime subject to crowding effects [16,[45][46][47][48], as intracellular therapeutics, suggests that this basic assembly mechanism should be considered. Figure A3.…”
Section: Discussionmentioning
confidence: 99%
“…The structures can also be utilized for transfecting small interfering RNA molecules (siRNA) for silencing genes in a controllable way. Kocabey et al [36] tried to silence a target gene by equipping a small PEGylated folate -modified DNA nanotube ( Figure 1C) with siRNA molecules, but did not succeed with that particular setup. However, Lee et al [37] showed that folate -or peptide -modified tetrahedral DNA nanoparticles loaded with siRNAs ( Figure 1C) can silence the target genes in tumors.…”
Section: Towards Dna-based Drug Delivery Vehicles and Advanced Therapmentioning
confidence: 99%
“…(B) DNA origami nanostructures for delivering doxorubicin (DOX) into cancer cells: an under-twisted rod-like shape [33], a straight rod [31] and a triangle [31,32]. (C) DNA structures for small interfering RNA (siRNA) delivery: a cage with cell-targeting ligands (folate or peptide) at the end of the siRNA motifs [37], and a PEGylated folatemodified nanotube [36]. (D) DNA structures for CpG-triggered immunostimulation: a DNA origami tube [39] and a polypod-like structure [41].…”
Section: Shape-complementarity-based Constructionmentioning
confidence: 99%
“…Folate modification promotes endocytosis into cancerous cells where folate receptors are overexpressed. DNA nanotubes produced by origami and tile‐based assembly methods that contained folate and fluorescently modified component strands recognized folate receptors on the cell surface, followed by internalization upon binding. This resulted in a tenfold uptake enhancement compared to unmodified origami‐based nanotubes.…”
Section: Cellular Delivery Of Dna Nanostructuresmentioning
confidence: 99%